Answer:
y + 1 =
(x - 1)
Explanation:
The equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
Calculate m using the slope formula
m =
![(y_(2)-y_(1) )/(x_(2)-x_(1) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/89lni2arad82a9125nchkq0vkwnbj1bzli.png)
with (x₁, y₁ ) = (1, - 1) and (x₂, y₂ ) = (5, 2)
m =
=
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)
using (a, b) = (1, - 1 ), then
y - (- 1) =
(x - 1) , that is
y + 1 =
(x - 1)